Survey on major diseases of vegetable and fruit crops in Chittagong region (Bangladesh Journal of Agricultural Research, 2010)
A survey was conducted during October 2006 to June 2008 to observe disease prevalence of vegetable and fruit crops in Chittagong region. Through the survey, 24 diseases with their incidence and severity were recorded. The average higher leaf infection in early blight of potato and fruit infection in soft rot of potato were recorded 37% and 39%, respectively. The highest leaf infection (43%) of early blight of tomato that was more frequented (mode) 36% in different locations with ±0.45% ranges (Standard error) for causing the disease as recorded at Sadar Anwara upazila of Chittagong. The highest fruit infection of soft rot of potato (43%) was recorded at Dohazari, Chandanaish upazila in Chittagong. The average of higher disease severity of leaf (27%) and fruit (33%) was recorded in early blight of tomato and soft rot of potato, respectively, and the highest disease severity of leaf (29%) and fruit (35%) was recorded in Phomopsis blight and early blight of tomato and soft rot of potato, respectively. Keywords: Diseases; vegetable; fruit; survey.DOI: 10.3329/bjar.v35i3.6449Bangladesh J. Agril. Res. 35(3) : 423-429